Impaired insight in schizophrenia is associated with higher frontoparietal cerebral blood flow: an arterial spin labeling study - Jianmeng Song; Edgardo Carmona-Torres; Yasaman Kambari; Sofia Chavez; Fumihiko Ueno; Teruki Koizum; Aron Amaev; Ali Abdolizadeh; Vincenzo De Luca; Daniel M. Blumberger; Gary Remington; Bruce Pollock; et al. (Schizophrenia)
Abstract Impaired insight into illness occurs in up to 98% of patients with schizophrenia, depending on the stage of illness, and leads to negative clinical outcomes. Previous neuroimaging studies suggest that impaired insight in patients with schizophrenia may be related to structural and functional anomalies in frontoparietal brain regions. To date, limited studies have investigated the association between regional cerebral blood flow (CBF) and impaired insight in schizophrenia. Therefore, we sought to investigate the relationship between regional CBF, as measured by arterial spin labeling (ASL), and impaired insight in participants with schizophrenia. A total of 32 participants were included in the analysis. Impaired insight in patients with schizophrenia was measured using the VAGUS, Self-report (VAGUS-SR). Resting-state regional CBF was measured using pseudo-continuous ASL (pCASL) and extracted using SPM12 and REX toolbox. Whole brain analysis found that impaired insight was associated with higher regional CBF in the right angular gyrus, left supramarginal gyrus, and right superior frontal region when controlling for age, gender, smoking status, and illness severity. The results indicate that impaired insight in schizophrenia is related to regional CBF in frontoparietal areas. These neuroimaging findings can serve as therapeutic targets for intervention, such as with non-invasive brain stimulation.